CAD-integrated design for manufacturing and assembly in mechanical design. Issue 3 (4th March 2022) - Campi, Federico; Favi, Claudio; Germani, Michele; Mandolini, Marco
ABSTRACT: Design for Manufacturing and Assembly (DfMA) is a consolidated engineering activity that suffers a real integration with 3D CAD systems. DfMA principles are currently applied downstream of the 3D modelling, by following the well-known rules available from the literature and company's know-how. The paper provides a method to acquire, elaborate and represent DfMA rules sets to aid designers and engineers in developing mechanical products. This research work wants to define a general method able to couple DfMA design guidelines (knowledge-based design) with geometrical product features available by the investigation of the 3D model. The analysis of the 3D CAD model allows to anticipate manufacturing issues and to control manufacturing cost during product design. Moreover, a framework to embed this approach within a 3D CAD system is presented for future development in a software tool. Two case studies, a simple casing made of six parts and a centrifugal pump made of sixty-eight parts, highlight how the proposed method allows easy deployment of this approach in DfMA projects. Several benefits are recognized: (i) anticipation of manufacturing and assembly issues, (ii) reduction of manufacturing and assembly cost and, (iii) reduction of effort and time required by designers during the product development process.